User Satisfaction Analysis of Netflix Application Using End User Computing Satisfaction (EUCS) Method - Kusnadi, Yahdi; Rahman, Iga Auliani (Universitas Mohammad Husni Thamrin, 2025)
Technology has changed many aspects of life, including economics, politics, government, and communication, which have an impact on people's lifestyles and views. One of these changes is the emergence of streaming services such as Netflix, which allows users to watch various shows and movies by subscribing. This study aims to measure Netflix user satisfaction using the End User Computing Satisfaction (EUCS) method. The EUCS method is used to compare user expectations and reality towards information systems. This study involved 50 respondents from various age groups and professions: 5 people aged 17–20 years, 38 aged 21–29, 6 aged 30–39, and 1 aged 40–49. In terms of occupation, there were 14 students, 3 housewives, 3 entrepreneurs, 25 employees, and 5 others. The majority of respondents have an income of 3–5 million rupiah. The results of the study showed that more than 80% of respondents stated